The Effect of Rewarming on the Cognitive Status of Patients After Open-heart Surgery: A Randomized Clinical Trial - Somayeh Haji-Jafari; Seyed Hossein Ahmadi Tafti; Ismail Azizi-Fini; Mahboubeh Rezaei; Fatemeh Atoof (Iran University of Medical Sciences, 2023)
Background: Hypothermia is usually used during cardiac surgery to further protect against cardiac and cerebral ischemia. However, cognitive impairment could be a common complication after open heart surgery. This study aims to determine the effect of rewarming on the cognitive status of patients after open heart surgery.  Methods: The present study was conducted as a double-blind, randomized clinical trial at Tehran Heart Center, Tehran, Iran. In this clinical trial, 80 patients referred for open heart surgery were selected and randomly assigned into the intervention (n=40) and control (n=40) groups. In the intervention group, rewarming the mattress was started after the patient entered the intensive care unit. Warming continued until the patient's body temperature reached the normothermia level (37°C to 37.5°C). The data were collected by demographic-clinical questionnaire and Mini-Mental State Examination at three time points: before, 7 days, and 1 month after the surgery. The data were analyzed in SPSS software, version 16 using descriptive statistics, independent t test, chi-square test, repeated measure ANOVA, and paired t test. The significance level was considered less than 0.05. Results: The difference between the mean±SD scores of cognitive status in the intervention group before the surgery (28.73±0.87), 7 days (27.63±1.03), and 1 month after the surgery (28.93±1.21) was significant (P=0.008). The difference between the mean±SD scores of cognitive status in the control group before the surgery (28.42±1.02), 7 days (26.61±0.86), and 1 month after the surgery (27.85±1.06) was also significant (P=0.042). The results indicated that the mean score of cognitive status improves after 1 month, and it is greater in the intervention group (F=20.37, df=2, P<0.001). Significant differences were observed between the first and second time of measurements (P<0.0001) and also the second and third time of measurements (P<0.0001). Conclusion: Rewarming patients after open heart surgery improves their cognitive status. Therefore, this procedure can be used as a safe and non-invasive method to prevent cognitive complications by nurses after open heart surgery.